Cotton Dust Exposure and Respiratory Disorders among TextileWorkers at a Textile Company in the Southern Part of Benin - HINSON, Antoine Vikkey; LOKOSSOU, GRATIEN; SCHLÜNSSEN, VIVI; AGODOKPESSI, GILDAS; Sigsgaard, Torben; FAYOMI, EBOUM BENJAMIN (My University, 2016)
The textile industry sector occupies a prominent place in the economy of Benin. It exposes workers to several occupational risks, including exposure to cotton dust. To assess the effect of exposure to cotton dust on the health of workers, this study was initiated and conducted in a Beninese cotton industry company. The objective of the study was to evaluate the respiratory disorders among the textile workers exposed to cotton dust and the cross-sectional study involved 656 subjects exposed to cotton dust and 113 non-exposed subjects. The methods used are mainly based on a survey using a questionnaire of organic dust designed by the International Commission of Occupational Health (ICOH); and on the measures of lung function parameters (FEV1 and FVC). The main results of the different analyzes revealed that subjects exposed to cotton dust have more respiratory symptoms than unexposed subjects (36.9% vs. 21.2%). The prevalence of chronic cough, expectorations, dyspnoea, asthma and chronic bronchitis are 16.8%, 9.8%, 17.3%, 2.6%, and 5.9% respectively among the exposed versus 2.6%, 0.8%, 16.8%, 0% and 0.8% among the unexposed subjects. The prevalence of byssinosis is 44.01%.The prevalence of symptoms is dependent on the sector of activity and the age of the subject. These results should encourage medical interventions and technical prevention especially since the textile industry occupies an important place in the Benin’s economy.
Keywords: respiratory disorders; cotton dust; byssinosis; FEV1; FVC; Benin